Student’s Interpersonal Communication Skills in Learning History of the 21st Century - Mardiani, Fitri; Subiyakto, Bambang; Safitri, Mulyani (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The aim of this research is to analyze the challenges and efforts of teachers in developing students' interpersonal communication skills in history learning at SMAN 8 Banjarmasin. This research uses a qualitative descriptive method. Data collection techniques through the stages of observation, interviews, and document study. Data collection was carried out purposively. Triangulation techniques were used to test the validity of the data. Meanwhile, the data analysis stages are carried out, which include collecting data, reducing data, presenting data, and coming to conclusions. As a result of the research, history teachers at SMAN 8 Banjarmasin agreed that interpersonal communication skills are an important element in encouraging activeness in history learning. However, in practice, there are several obstacles such as students' difficulties when expressing ideas, shyness, and lack of confidence in conveying arguments during discussions. Therefore, history teachers try to develop students' interpersonal communication skills by providing examples of good communicators, being attentive listeners, and creating a sense of security and comfort through strengthening literacy.